A Case of Primary Hyperparathyroidism due to Intrathyroidal Parathyroid Cyst. (29th December 2014) - Yalcin, Yavuz; Mete, Turkan; Aktimur, Recep; Kucuk, Gultekin Ozan; Duman, Gulhan; Ozbalci, Aysu Basak; Alici, Omer
Abstract : Parathyroid cysts constitute 0.08–3.41% of all parathyroid masses. Intrathyroidal parathyroid cysts, however, are rare conditions with only a few cases being reported. Most of the parathyroid cysts are found to be nonfunctional and functional cysts are generally thought to be due to cystic degeneration of parathyroid adenomas. A cystic, smooth contoured lesion of 24 × 19 × 16 mm was observed in left thyroid lobe of a 76-year-old woman during ultrasonography which was performed as routine workup for primary hyperparathyroidism. It was defined as a cystic thyroid nodule at first. Tc 99m sestamibi scintigraphy was performed to see any parathyroid lesions, but no radioactive uptake was observed. Intact parathormone (iPTH) level was found to be >600 pg/mL in cyst aspiration fluid. Left lobectomy was performed, with a diagnosis of primary hyperparathyroidism due to functional parathyroid cyst. Serum iPTH level was decreased >50% postoperatively and histopathological evaluation was consistent with an encapsulated parathyroid adenoma with a cystic center. Parathyroid cysts are among rare causes of primary hyperparathyroidism. Diagnosis is made by markedly increased iPTH level in cyst fluid and observation of parathyroid epithelium lining the cyst wall.